2018
DOI: 10.1111/voxs.12427
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hepatitis B and hepatitis C seroprevalence among blood donors – Haiti, 2005‐2014

Abstract: Background and Objectives Data on the seroprevalence of viral hepatitis are limited in Haiti; consequently, the epidemiology is poorly described. This study aims to provide a descriptive analysis of hepatitis B virus (HBV) and hepatitis C virus (HCV) seroprevalence of blood donations in Haiti. Materials and Methods Using Haiti’s National Blood Safety Program and Haitian Red Cross reports from 2005 to 2014, we analysed the results of screening tests of donor serum samples to assess HBV and HCV seroprevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[8][9][10][11] A longitudinal study conducted among blood donors during 2005-2014 reported decreasing HBsAg prevalence from 3.95% in 2005 to 3.42% in 2014. 12 Among pregnant women in Haiti, the HBsAg prevalence was 5% in a study conducted in 2006 and 2.5% (95% CI: 1.7-3.4) in a study conducted in 2012. 13,14 Haiti is the only country in the AMR that is highly endemic for HBV (HBsAg prevalence > 7%).…”
Section: Introductionmentioning
confidence: 92%
“…[8][9][10][11] A longitudinal study conducted among blood donors during 2005-2014 reported decreasing HBsAg prevalence from 3.95% in 2005 to 3.42% in 2014. 12 Among pregnant women in Haiti, the HBsAg prevalence was 5% in a study conducted in 2006 and 2.5% (95% CI: 1.7-3.4) in a study conducted in 2012. 13,14 Haiti is the only country in the AMR that is highly endemic for HBV (HBsAg prevalence > 7%).…”
Section: Introductionmentioning
confidence: 92%
“…Differences were found when analyzing the prevalence of HBsAg by continent of origin, even compared to other investigations carried out in the countries that mostly comprised the sample, such as Haiti and Venezuela [ 18 , 19 , 43 ]. In the present study, in Central America (n = 198), where Haitians predominated (89.4%), the frequency of HBsAg was 8.6% (n = 17/198; 95% CI: 5.4–13.3%), while among participants from South America (n = 152), especially Venezuelans (87.2%), it was 3.3% (n = 5/152; 95% CI: 1.4–7.5%).…”
Section: Discussionmentioning
confidence: 64%
“… * EIA confirmed by CMIA if the type of assay is unchanged from the report by Jean-Baptiste et al ( 34 ). § Data based on report from state refugee health coordinators.…”
Section: Resultsmentioning
confidence: 95%
“… * EIA confirmed by CMIA if the type of assay is unchanged from the report by Jean-Baptiste et al ( 34 ). AIDS, acquired immunodeficiency syndrome; ANC, antenatal clinic; CMIA, chemiluminescence microparticle immunoassay; EIA, enzyme immunoassay; HCV, hepatitis C virus; HIV, human immunodeficiency virus; N/R, not reported; PAHO, Pan American Health Organization; RCT, randomized controlled trial; RDT, rapid diagnostic test; SD, standard deviation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation